Myopericarditis by SARS-CoV-2: A Case Report - Antunes, Eulália; Lopes, Joana; Campinho Ferreira, Carla; Caridade, Sofia; Gomes, Vânia; Silva, Isabel (Gazeta Médica, 2024)
SARS-CoV-2 infection can be followed by several cardiovascular complications such as pulmonary thromboembolism, myocardial injury and pericarditis. This case refers to a 48-year-old man with a one year history of unstable angina who presented to the emergency department with chest pain, dyspnea, dry cough and fever. He was admitted with the diagnosis of pulmonary thromboembolism associated with pulmonary infarction and pneumonia. During hospitalization he developed chest pain. The electrocardiogram showed slight elevation of the ST segment with superior concave slop in the inferior and lateral leads and depression of the PR interval. In addition, there was an increase in myocardial necrosis markers, raising the suspicion of myopericarditis. Given a history of flu-like syndrome in the 3 weeks before admission, he collected serology for SARS-CoV-2 with an IgG value > 100 u/mL (cut-off of 10 u/mL). Lysine acetylsalicylate was started with resolution of chest pain. Three months later, the patient was asymptomatic with reversal of the electrocardiographic findings.